Execution of single minute exchange of die on corrugation machine in cardboard box manufacturing company: a case study. (2016) - Garg, Gaurav; Gupta, Ajay; Mor, Rahul S.; Trehan, Rajiv
In the present global competitive market, it is most important for industries to work efficiently and adopt contemporary management practices like lean manufacturing, process integration and inter-organisational collaborations in order to meet their corporate goals. In developing countries like India, automation of production processes is under evolution especially for small scale companies. For this kind of industry, it is very important to properly utilise the available resources (machinery, labour, raw material) and eliminating all the non-value-added operations. In this context tools like SMED plays a significant role to facilitate an organisation in becoming more responsive and competitive by reducing setup/changeover time. This paper discusses the implementation of SMED in a corrugated cardboard box manufacturing company. The application of SMED resulted in reduction of 86.6% in setup/changeover time and hence a significant saving in cost. This was achieved with very little investment.